2012
DOI: 10.1016/j.febslet.2012.06.054
|View full text |Cite
|
Sign up to set email alerts
|

miR‐615‐5p is restrictedly expressed in cirrhotic and cancerous liver tissues and its overexpression alleviates the tumorigenic effects in hepatocellular carcinoma

Abstract: a b s t r a c t microRNAs aberrant behavior in heptocellular carcinoma (HCC) plays a major role in HCC pathogenesis. miR-615-5p expression has never been evaluated in HCC. We showed that miR-615-5p was preferentially expressed in HCC, cirrhotic liver tissues and HCC cell lines, but undetected in normal livers. Forced miR-615-5p expression in HCC cell lines led to significant decrease in cell growth and migration. In-silico predication revealed insulin-like growth factor-II (IGF-II) as a potential downstream ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…A ratio of ~2.0 is generally accepted as 'pure' for RNA. Thus, RNA samples with absorbance values outside the range of 1.8-2 were excluded from the study, as previously described (20,25 (20,25).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A ratio of ~2.0 is generally accepted as 'pure' for RNA. Thus, RNA samples with absorbance values outside the range of 1.8-2 were excluded from the study, as previously described (20,25 (20,25).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent to incubation for 5 h, formazan (MTT metabolic product) was re-suspended in 200 µl dimethyl sulfoxide. Colorimetric measurements and absorbance were performed using a Wallac 1420 Victor2 Multilabel Counter (Perkin Elmer Inc., Waltham, MA, USA), as previously described (20,25).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential regulation of IGF axis members by microRNAs is an appealing subject of investigation. We have previously shown that miR-615-5p downregulates IGF-Ⅱ expression and forcing its expression reduces tumorigenesis in HCC [14] . miR-122 was found to suppress IGF-1R expression thus inhibiting HCC progression [15,16] .…”
Section: Introductionmentioning
confidence: 99%